Dopamine, Cognitive Impairments and Second-Generation Antipsychotics: From Mechanistic Advances to More Personalized Treatments - Sebastiano Alfio Torrisi; Samuele Laudani; Gabriella Contarini; Angelina De Luca; Federica Geraci; Francesca Managò; Francesco Papaleo; Salvatore Salomone; Filippo Drago; Gian Marco Leggio (MDPI AG, 2020)
The pharmacological treatment of cognitive impairments associated with schizophrenia is still a major unmet clinical need. Indeed, treatments with available antipsychotics generate highly variable cognitive responses among patients with schizophrenia. This has led to the general assumption that antipsychotics are ineffective on cognitive impairment, although personalized medicine and drug repurposing approaches might scale down this clinical issue. In this scenario, evidence suggests that cognitive improvement exerted by old and new atypical antipsychotics depends on dopaminergic mechanisms. Moreover, the newer antipsychotics brexpiprazole and cariprazine, which might have superior clinical efficacy on cognitive deficits over older antipsychotics, mainly target dopamine receptors. It is thus reasonable to assume that despite more than 50 years of elusive efforts to develop novel non-dopaminergic antipsychotics, dopamine receptors remain the most attractive and promising pharmacological targets in this field. In the present review, we discuss preclinical and clinical findings showing dopaminergic mechanisms as key players in the cognitive improvement induced by both atypical antipsychotics and potential antipsychotics. We also emphasize the concept that these mechanistic advances, which help to understand the heterogeneity of cognitive responses to antipsychotics, may properly guide treatment decisions and address the unmet medical need for the management of cognitive impairment associated with schizophrenia.